Analisa Quality Of Service Dan Implementasi Voice Over Internet Protocol Dengan Menggunakan IPSEC VPN - Melyana, Ingrid; Indriyani, Tutuk (INTEGER: Journal of Information Technology, 2016)
At present technology, specifically in telecommunication sector, develops very rapidly, and mainly adopts Internet Protocol (IP) to support the communication network. In IP networks it involves voice communication commonly called Voice over Internet Protocol (VoIP). It the development of telephone communication using IP networks as paths of data transfer. As it is an open source, its network security becomes a crucial issues in VoIP. One of the ways to cope with the security problems is to adopt Intenet Protocol Security (IPSec) in VoIP networks. The communication trials used two different bandwidths – 375 kbps and minimum bandwidth standard – codec G.711 u. The result of the analysis showed that the trial using minimum bandwidth standard – codec G.711 u was not suitable to be applied in VoIP IPSec network, as in average it had package loss by 58.75%. Accordingly, the VoIP IPSec networks with 375 kbps bandwidth were more superior. In average, with delay rate (3,4956 ms), jitter (6,8894 ms) and package loss (0,00%). In conclusion, VoIP IPSec networks requires large bsndwidth, i.e. : minimally 375 kbps in its operation.